Evidence of the internal structure of the brazilian version of the Global Assessment ff Individual Needs Scale - Short Screener - Barbosa, Guilherme Correa; Rebustini , Flávio Rebustini; de Oliveira, Márcia Aparecida Ferreira (Disciplinarum Scientia | Saúde, 2026)
Objective: To find evidence of the internal structure of the Global Assessment of Individual Needs-Short Screener (Portuguese version), obtained during the care of users of alcohol and other drugs in CAPSadII, by means of Explanatory Factor Analysis (EFA). Method: The study sample consisted of 200 users of the Alcohol and Other Drugs Psychosocial Care Center (CAPSadII) with an average age of 39.08. Exploratory and Confirmatory Factor Analysis were applied. Results: The results for both techniques indicated that the unidimensional model presents more precise levels of measurement compared to the model with 4 domains. The one-dimensional model had a variance of 56.91% and better factor loadings and model fit indices. Conclusion: The instrument shows evidence of a consistent and reliable internal structure, with a balanced assessment of the severity of individuals, with items well distributed along the spectrum.